The Influence of Capital Market Training, Investment Knowledge, and Investment Benefits on Investment Interest Among Students in Religious Higher Education Institutions - Bernando, Franky Okto; Pringgondani, Pringgondani; Nugraha, Deni Pandu (Journal of Nonformal Education, 2026)
Background: Indonesia’s capital market faces a critical challenge with foreign investors dominating 51.99% of top issuers, highlighting an urgent need to cultivate domestic investor participation. Research Objectives: This study investigates how capital market training, investment knowledge, and perceived benefits influence investment interest among students in Islamic universities, aiming to identify effective strategies for faith-based financial education. Research Method: Employing a quantitative approach, we surveyed 136 members of Sharia Investment Galleries across three state Islamic universities (UIN Jakarta, Bandung, and Banten) and analyzed data using PLS-SEM. Research Findings: The findings highlight the psychological importance of perceived returns and value creation as key influencers. At the same time, it also reveals the effectiveness of Sharia-compliant investment benefits in religious academic settings, where ethical alignment strengthens financial engagement. These insights underscore the interplay of cognitive preparation and value-driven incentives in fostering sustainable investment participation, offering valuable guidance for financial educators and policymakers aiming to promote informed and motivated investment decisions. Conclusion: The study concludes that capital market training, investment knowledge, and perceived benefits significantly enhance investment interest. Additionally, emphasizing the advantages of Sharia-compliant investments proves particularly effective in religious academic environments. Novelty/Originality/Value: This study pioneers the validation of capital market training (KSPM) in Islamic universities, revealing how religious values shape investment behavior. It introduces the groundbreaking Faith-Smart KSPM framework, blending Islamic finance principles with modern investment education to develop ethical investors. The findings offer regulators a strategic approach to boost domestic investment while aligning with Indonesia’s financial sovereignty goals.